Prediksi Pasien Covid-19 yang Meninggal di Jawa Timur Menggunakan Metode Regresi Spline Truncated - Aini, Qurrotul; Yulianto, Tony; Faisol, Faisol (Universitas Islam Madura, 2022)
Corona Virus Disease 2019 (COVID-19) was first discovered at the end of 2019 in Wuhan, China. The virus attacks the respiratory system with pneumonia-like symptoms. This virus is classified as a new virus so it does not have an antidote and has spread throughout the world until it is out of control. There are more than 200 countries reporting covid-19 cases including Indonesia. Because the biggest effect of COVID-19 is death, so researchers need to predict whether the mortality rate of COVID-19 patients. One method for predicting covid-19 patients who died in East Java is using the spline truncated regression method. Spline regression is a regression analysis that is able to estimate data that does not have a specific pattern and has a tendency to seek data estimates fro, the formed pattern on its own, while truncated is a function that can be interpreted as a function of slice. And produces a GCV value of 51.0167, a MAPE value 47.0096, MSE 32.9825, and R-Sq 0.9998. Based on the MAPE value, the prediction model is said to be still reasonable.